2020
DOI: 10.1128/aac.00224-20
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Cost and Compensatory Evolution in Levofloxacin-Resistant Mycobacterium aurum

Abstract: We isolated spontaneous levofloxacin-resistant strains of Mycobacterium aurum to study the fitness cost and compensatory evolution of fluoroquinolone resistance in mycobacteria. Five of six mutant strains with substantial growth defects showed restored fitness after being serially passaged for 18 growth cycles, along with increased cellular ATP level. Whole-genome sequencing identified putative compensatory mutations in the glgC gene that restored the fitness of the resistant strains, presumably by altering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The lack of corelation between the magnitude of resistance and the proportion of a population containing a minor resistance conferring allele (Figure 2a-d) is consistent with the suggestion that gyrA D94G and A90V do not contribute a significant fitness cost 15 .…”
Section: Discussionsupporting
confidence: 85%
“…The lack of corelation between the magnitude of resistance and the proportion of a population containing a minor resistance conferring allele (Figure 2a-d) is consistent with the suggestion that gyrA D94G and A90V do not contribute a significant fitness cost 15 .…”
Section: Discussionsupporting
confidence: 85%
“…Antibiotic resistance usually causes bacterial growth defects or weakened virulence, called fitness costs, owing to production and maintenance of resistance machinery (Wang et al, 2019;Pi et al, 2020;Balbontín et al, 2021). Susceptible bacterial populations usually outcompete resistant ones in the absence of antibiotics because of the fitness cost (Pacheco et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Gyrase is a heterotetramer comprising two GyrA and two GyrB subunits, catalyzing a DNA double-strand break, passing another DNA strand through the break, and resealing it (Hooper and Jacoby, 2015). Mutations in gyrA and gyrB, known as quinoloneresistance-determining regions, can cause bacterial resistance to LVX (Pi et al, 2020). The SNP and InDel analyses based on WGS showed that one nonsynonymous SNP and one InDel mutations occurred in gyrB (PA0004) and gyrA (PA3168) of the PAS81 strain, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Rifampin (RIF) rpoB rpoA, rpoC (Telenti et al, 1993;Ohno et al, 1996;Ramaswamy and Musser, 1998;Comas et al, 2011;Shea et al, 2021) Pyrazinamide (PZA) pncA pnaB2 (epistatic) (Konno et al, 1967;Scorpio and Zhang, 1996;Muzondiwa et al, 2021) Para-aminosalicylic acid (PAS) thyA thyX-hsdS.1 intergenic region associated, but not shown to be compensatory (Rengarajan et al, 2004;Zhang et al, 2013;Coll et al, 2018) Ethambutol (EMB) embCAB operon aftA (Rv3792) (Alcaide et al, 1997;Telenti et al, 1997;Safi et al, 2013) Isoniazid (INH) katG, inhA ahpC promoter (Zhang et al, 1992;Heym et al, 1995;Sherman et al, 1996) Fluoroquinolones (FQ) gyrA Extragenic Rv0890c, Insertions in glgC in Mycobacterium aurum (Takiff et al, 1994;Pi et al, 2020) Bedaquiline (BDQ) mmpR (Rv0678), atpE, pepQ atpB? (suggested) (Andries et al, 2005;de Jonge et al, 2007;Huitric et al, 2010;Andries et al, 2014;Nieto Ramirez et al, 2020) Clofazimine (CFZ) pepQ, mmpR Unknown (Almeida et al, 2016) Pretomanid (PA-824)/ Delaminid (DLM)…”
Section: Compensatory Mechanism Referencesmentioning
confidence: 99%